Identification of kinematic hardening parameters for mild steel by cyclic loading - Muhammad Zakiran, Abd Aziz (2013)
This report presents an identification of kinematic hardening parameters for mild steel by cyclic loading. Metal bending is one of the most common processes to change the shape of material by plastically deforming. A complete theory and reliable simulation has been developed to improve spring-back prediction. One of the areas that can be improved is to provide reliable material parameter inputs into the simulation software. The aims of this report are to fabricate new cyclic loading tool and identify of kinematic hardening parameters for mild steel by cyclic loading. Cyclic loading test have been conducted to determine the kinematic hardening parameters. The first step in the parameter identification process is to conduct the cyclic loading test and record load-extension data. The data converted to stress-strain data by using force analysis. The stress-strain data are optimized by using kinematic hardening equation. Once the stress-strain data have been optimized, the kinematic parameters are identified. The values of kinematic hardening parameters are relatively high but still acceptable because the recorded R square above 0.9.